IDENTIFICATION AND SELECTION OF SIX SIGMA PROJECTS - Flifel, Abdalhkeim FA.; Zakić, Nebojša; Tornjanski, Aleksandra (Journal of process management and new technologies, 2017)
Six Sigma is a well-structured and proven methodology for improving organizational performance. It helps achieving the goals of the organization through the use of project-driven approach. The implementation of Six sigma approach depends on proper identification and selection of projects, moreover, the selection of right Six sigma projects is one of the critical success factors of six sigma efforts. The paper provides the sources for the identification of potential projects, top down and bottom up approaches, the process of selection of projects, guidelines that assist the selection of appropriate projects, selection criteria which must be precisely chosen in accordance with the objectives, needs and capabilities of the organization as well as sophisticated techniques and tools recommended in the literature for the selection of projects.